Behcet's disease without oral ulcers presenting with erythema nodosum and deep venous thrombosis. (January 2016) - Ajmani, Sajal; Chowdhury, Abhra Chandra; Misra, Durga Prasanna; Agarwal, Vikas
We present a young male with recurrent erythema nodosum and recent deep vein thrombosis with scrotal ulcers but no oral ulcers. He was diagnosed as having Behcet's disease (BD) and subsequently responded to immunosuppressants and anticoagulation. This case highlights that up to 2% patients with BD may not have oral ulcers. Timely institution of therapy in our patient resulted in a favorable outcome.